Oil and mucilage idioblasts co-occur in the vegetative organs of Ocotea pulchella (Lauraceae): comparative development, ultrastructure and secretions - de Deus Bento, Karla Bianca [UNESP]; Canaveze, Yve; Machado, Silvia Rodrigues [UNESP] (Springer Nature, 2024)
This study compares oil and mucilage idioblasts occurring together in the vegetative organs of Ocotea pulchella, a Lauraceae species. Our focus is specifically on the ontogeny and developmental cytology of these secretory cells. Both types of idioblasts originate from solitary cells located in the fundamental meristem, underlying the protodermis. The growth of both types of idioblasts is asynchronous, with the oil idioblasts developing first, but their initiation is restricted to the early stages of organ development. Mucilaginous idioblasts occur exclusively in the palisade parenchyma, while oil idioblasts are scattered throughout the mesophyll, midrib, and petiole of the leaves. The lamellar secretion of mucilage idioblasts is mostly made up of polysaccharides, while the secretion of oil idioblasts is made up of terpenes and lipids. Cupule occurred only in the oil idioblasts, while suberized layers occurred in both types of cells. We found that immature oil idioblasts that are close to each other fuse; mature mucilage idioblasts have labyrinthine walls arranged in a reticulate pattern; the cells close to the oil idioblasts have a pectin protective layer; and the oil idioblasts have a sheath of phenolic cells. In contrast to previous reports, the two types of secretory idioblasts were recognized during the early stages of their development. The results emphasize the importance of combining optical and electron microscopy methods to observe the ontogenetic, histochemical and ultrastructural changes that occur during the development of the secretory idioblasts. This can help us understand how secreting cells store their secretions and how their walls become specialized.
Keywords: Lauraceae; Mucilage-secreting cells; Oil-secreting cells; Ontogeny; Secretion; Suberized layer; Ultrastructure